Cover Image: Volume 22, Issue 4. Issue 4 (27th July 2020) - Leigh, Nicholas D.; Sessa, Sofia; Dragalzew, Aline C.; Payzin‐Dogru, Duygu; Sousa, Josane F.; Aggouras, Anthony N.; Johnson, Kimberly; Dunlap, Garrett S.; Haas, Brian J.; Levin, Michael; Schneider, Igor; Whited, Jessica L.
Abstract : The cover image is based on the Original Article von Willebrand Factor D and EGF Domains is an evolutionarily conserved and required feature of blastemas capable of multi‐tissue appendage regeneration by Jessica Whited, Kimberly Johnson, Duygu Payzin‐Dogru et al., https://doi.org/10.1111/ede.12332 .